Conflict resolution strategies : influence of organizational and professional commitment nurses - Pinho, Paula (2016)
Introduction: The changes in the health area and the set of structural changes in the nursing profession and career interfere in the dynamics and stability of the future of the nurses. Objectives: To study the influence of organizational and professional commitment of the nurses in the strategies of conflict resolution. Methods: This is a quantitative, transversal and non-experimental research, following a descriptive-correlational way. Data were obtained by applying a questionnaire to nurses that work on different types of Primary Health Care Units. As measuring instruments we used three scales that grouped a total of nine subscales used to evaluate: the organizational commitment, the professional commitment and the strategies of conflict resolution. Results: The majority of nurses present moderate scores of organizational and Professional commitment with higher affective commitment to the normative commitment or instrumental commitment and feel that nursing is an interesting and challenging profession, but personal and social perception of nursing relevance is moderately weak. Nurses adopt the domination conflict resolution strategies and accommodation over the head and less integrative strategies and commitment. With subordinates more nurses adopt the avoidance strategy. When the conflictual situation arises with colleagues more endow the integrative strategies and commitment and less domination strategy. The organizational and professional commitment is significantly associated with some solving strategies conflict adopted by nurses as the conflictual situation arises with the boss, with subordinates or colleagues. Some dimensions of organizational commitment and professional foretell to significantly shape the adoption of conflict resolution strategy adopted.